Chrysanthemum mutant for year-round flower production - Kumar, Gunjeet; Tiwari, A K; Vanlalruati, Vanlalruati (Indian Horticulture, 2019)
The morphological characters of yellow colour mutant are similar to that of Pusa Anmol, except for flower colour which is Yellow group 5A as per RHS colour chart against Orange group 26A in Pusa Anmol. The yellow colour mutants flowers throughout the year except June-July, showing photo-thermo insensitivity. The cultivation of such genotypes will save a lot of energy and resources to be employed to curb temperature and provide short-day photo period for off-season production of flowers.